Electrical and photoelectrical properties of n-InSe/p-CuInSe₂ optical contact - Kovalyuk, Z.D.; Sydor, O.M.; Netyaga, V.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2004)
Photosensitive heterojunctions were created by the method of optical contact of layered semiconductor InSe to CuInSe₂ plates. Due to high quality of contacting surfaces, a strong and enough perfect electrical junction is formed. To understand processes occurring in such heterojunctions, the measurements of current-voltage characteristics in forward and reverse directions, photoelectric modification of the direct branch of the current-voltage characteristic, capacitance-voltage characteristic, spectrum of the relative quantum efficiency have been carried out at the room temperature. The structures had a well-pronounced photovoltaic effect – the open-circuit voltage was 0.5 V and the short-circuit current density – 0.7 mА/cm². The conclusion about possibility of application of the obtained heterojunctions as photodetectors is made.